Respuesta :
Expressions are equal to 0 when x = –1 :
- 1. 4(x+1) : (4x+5)
- 3. 4(x-(-1) : (4x+5)
- 5. 4(x+1) : (5-4x)
Further explanation
Calculation operations include multiply, divide, add, substract, etc.
In mathematical operations we can use the order of operation / calculation according to the principle of PEMDAS
- P: Parentheses ⇒ ( )
- E: Exponents (powers, square roots, etc.)⇒√,²
- MD: Multiplication and Division ⇒ x and :
- AS: Addition and Subtraction ⇒ + and -
We use the principle of the number 0 which is, if the number 0 divided by any number will produce the number 0 as well
Let see the answer choices : (x = -1)
1. 4 (x plus 1) Over (4 x plus 5)
we translate this sentence into Algebraic expressions:
[tex]\displaystyle 4(x+1)\div(4x+5)\\\\=4(-1+1)\div(4.-1+5)\\\\=4(0)\div(-4+5)\\\\=0\div1\\\\=0[/tex]
2. 4 (x minus 1) Over (5 minus 4 x)
we translate this sentence into Algebraic expressions:
[tex]\displaystyle 4(x-1)\div(5-4x)\\\\=4(-1-1)\div(5-4.-1)\\\\=4(-2)\div(5+4)\\\\=-8\div9\\\\\neq 0[/tex]
3. 4 (x minus (minus 1)) Over (4 x plus 5)
we translate this sentence into Algebraic expressions:
[tex]\displaystyle 4(x-(-1)\div(4x+5)\\\\=4(-1+1)\div(4.-1+5)\\\\=4(0)\div(-4+5)\\\\=0\div1\\\\=0[/tex]
4. 4 (x plus (minus 1)) Over (4 x plus 5)
we translate this sentence into Algebraic expressions:
[tex]\displaystyle 4(x+(-1)\div(4x+5)\\\\=4(-1-1)\div(4.-1+5)\\\\=4(-2)\div(-4+5)\\\\=-8\div1\\\\\neq 0[/tex]
5. 4 (x plus 1) Over (5 minus 4 x)
we translate this sentence into Algebraic expressions:
[tex]\displaystyle 4(x+1)\div(5-4x)\\\\=4(-1+1)\div(5-4(-1))\\\\=4(0)\div(5+4)\\\\=0\div9\\\\=0[/tex]
Learn more
The numerical coefficient
https://brainly.com/question/11050477
Keywords : an algebraic expression , equal to 0
#LearnWithBrainly